The Magnetosphere‐Ionosphere Electron Precipitation Dynamics and Their Geospace Consequences During the 17 March 2013 Storm. Issue 8 (5th August 2019) - Khazanov, George V.; Chen, Margaret W.; Lemon, Colby L.; Sibeck, David G.
Abstract: During geomagnetic storms and substorms, the magnetosphere and ionosphere are strongly coupled by precipitating magnetospheric electrons from the Earth's plasma sheet and driven by both magnetospheric and ionospheric processes. Magnetospheric wave activity initiates electron precipitation, and the ionosphere and upper atmosphere further facilitate this process by enhancing the value of precipitated energy fluxes via connection of two magnetically conjugate regions and multiple atmospheric reflections. This paper focuses on the resulting electron energy fluxes and affiliated height‐integrated Pedersen and Hall conductances in the auroral regions produced by multiple atmospheric reflections during the 17 March 2013 geomagnetic storm and their effects on the inner magnetospheric electric field and ring current. Our study is based on the magnetically and electrically self‐consistent Rice Convection Model‐Equilibrium of the inner magnetosphere with SuperThermal Electron Transport modified electron energy fluxes that take into account the electron energy interplay between the two magnetically conjugate ionospheres. SuperThermal Electron Transport‐modified energy flux in the Rice Convection Model‐Equilibrium leads to a significant difference in the global conductance pattern, ionospheric electric field formation, Birkeland current structure, ring current energization and its energy content, subauroral polarization drifts intensifications and their spatial locations, interchange instability redistribution, and overall energy interplay on the global scale. Key Points: Simulated magnetospheric dynamics depends on the pattern and intensity of electrons precipitating into the atmosphere Precipitating electron energy fluxes enhanced by multiple atmospheric reflections affect ionospheric conductance Reduced electric field shielding at low L can lead to an increase in modeled ring current energy content